Exponential Stability of Difference Equations with Several Delays: Recursive Approach - Braverman Elena (Advances in Difference Equations, 2009)
We obtain new explicit exponential stability results for difference equations with several variable delays and variable coefficients. Several known results, such as Clark's asymptotic stability criterion, are generalized and extended to a new class of equations.